2023
DOI: 10.3390/biology12081052
|View full text |Cite
|
Sign up to set email alerts
|

White LED Lighting Increases the Root Productivity of Panax ginseng C. A. Meyer in a Hydroponic Cultivation System of a Plant Factory

Abstract: To identify effective light spectra for increasing the productivity of Panax ginseng, we conducted experiments in a controlled environment using a hydroponic cultivation system in a plant factory. We investigated the effect of single LEDs (red, blue, and yellow) and mixed LEDs (red + blue and red + blue + white). The relationships between four light spectra (red, blue, yellow, and white) and physiological responses (net photosynthetic rate, stomata conductance, transpiration rate, and intercellular CO2 partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Modarelli et al [13] proposed that aquaponics is suitable for leafy crops such as basil (Ocimum basilicum) due to the reduced utilization Plants 2024, 13, 463 2 of 13 of chemical fertilizers and increased productivity. Kim et al [14] reported that treating one-year-old ginseng with light-emitting diodes (LEDs) increased the weight of shoots in the cultivation chamber. Several studies have also analyzed the phytochemicals in ginseng cultivated using smart-farm systems.…”
Section: Introductionmentioning
confidence: 99%
“…Modarelli et al [13] proposed that aquaponics is suitable for leafy crops such as basil (Ocimum basilicum) due to the reduced utilization Plants 2024, 13, 463 2 of 13 of chemical fertilizers and increased productivity. Kim et al [14] reported that treating one-year-old ginseng with light-emitting diodes (LEDs) increased the weight of shoots in the cultivation chamber. Several studies have also analyzed the phytochemicals in ginseng cultivated using smart-farm systems.…”
Section: Introductionmentioning
confidence: 99%
“…Notable studies in this field include those examining the impact of light conditions on plant development [21,23], the use of hydroponic systems for enhancing ginseng quality with LED lighting [24], and the broader application of RSM in optimizing experimental conditions [25]. However, the integration of these elements in a single study, particularly with a focus on ginseng and its bioactive compounds, represents a distinctive contribution that sets the current work apart from existing research.…”
Section: Introductionmentioning
confidence: 99%